2020
DOI: 10.1038/s41598-020-60617-y
|View full text |Cite
|
Sign up to set email alerts
|

Asc-1 Transporter (SLC7A10): Homology Models And Molecular Dynamics Insights Into The First Steps Of The Transport Mechanism

Abstract: The alanine-serine-cysteine transporter Asc-1 regulates the synaptic availability of d-serine and glycine (the two co-agonists of the NMDA receptor) and is regarded as an important drug target. To shuttle the substrate from the extracellular space to the cytoplasm, this transporter undergoes multiple distinct conformational states. In this work, homology modeling, substrate docking and molecular dynamics simulations were carried out to learn more about the transition between the "outwardopen" and "outward-open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The first and the sixth helix are discontinuous and consist of two short α‐helices connected by a highly conserved unwound segment, which is involved in the substrate binding site and therefore in the transport translocation mechanism. The transporter primarily mediates the efflux of d‐serine and glycine through the hetero‐exchange with other neutral amino acids, and thus regulates glutamatergic neurotransmission and synaptic plasticity in the forebrain, and is probably also involved in the control of glycinergic transmission in the brainstem and spinal cord (Errasti‐Murugarren & Palacín, 2022; Eulenburg & Hülsmann, 2022; Mikou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first and the sixth helix are discontinuous and consist of two short α‐helices connected by a highly conserved unwound segment, which is involved in the substrate binding site and therefore in the transport translocation mechanism. The transporter primarily mediates the efflux of d‐serine and glycine through the hetero‐exchange with other neutral amino acids, and thus regulates glutamatergic neurotransmission and synaptic plasticity in the forebrain, and is probably also involved in the control of glycinergic transmission in the brainstem and spinal cord (Errasti‐Murugarren & Palacín, 2022; Eulenburg & Hülsmann, 2022; Mikou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…From those 402 variants, one stop-gain variant (predicted to have a high impact), one stop-loss variant (predicted to have a high impact), and seven missense variants (predicted to have a moderate but deleterious impact; all other 128 missense variants were predicted to be tolerated) were further analysed (the other Resources (Hunt et al, 2018) (suggesting a very low minor allele frequency), is located in exon 1 which is part of the MANE (Morales et al, 2022) transcript (correct annotation) and present in all canine transcript variants [affecting all isoforms; NCBI Gene (NCBI Resource Coordinators, 2018)], and clearly affects the protein structure (creating a stop codon at the N-terminal part of the protein; Figure 2c). SLC7A10 can be involved in the observed phenotype as it is a neuronal transporter (Errasti-Murugarren & Palacín, 2022; Eulenburg & Hülsmann, 2022;Mikou et al, 2020;Safory et al, 2015) whose deletion causes neurological abnormalities in knock-out mice (Safory et al, 2015;Xie et al, 2005) and is considered as a candidate gene for stiff-person syndrome (Ehmsen et al, 2016). Since none of the other variants meet all these criteria, this nonsense variant was considered as the most promising candidate disease-causing variant.…”
Section: Genetic Analysismentioning
confidence: 99%
“…The NMDA receptor has previously been linked to diseases such as schizophrenia and Alzheimer’s ( Cheng et al, 2021 ), and several studies have therefore investigated the effects of pharmacologic SLC7A10 inhibition on SLC7A10 function related to the transport of both D- and L-stereoisomers of small neutral amino acids in the brain ( Brown et al, 2014 ; Sason et al, 2016 ; Errasti-Murugarren and Palacín, 2021 ). SLC7A10 is present in both astrocytes and neurons ( Mikou et al, 2020 ) and has been found to be responsible in particular for D-serine and glycine release, as well as D- and L-serine uptake ( Rutter et al, 2007 ; Rosenberg et al, 2013 ; Safory et al, 2015 ; Sakimura et al, 2016 ; Sason et al, 2016 ; Mikou et al, 2020 ). Reduced glycine but not D-serine levels were observed in the nervous system of Slc7a10 knockout mice ( Safory et al, 2015 ).…”
Section: Emerging Metabolic Functions Of Slc7a10mentioning
confidence: 99%
“…154 With the advancement in the cryo-EM and X-ray crystallography technologies, great achievements have been achieved in the structural elucidation of membrane transport proteins. 155 The structure analysis of transport protein by molecular dynamics simulation and singlemolecule fluorescence resonance energy transfer imaging clarified the more specific molecular mechanism of electrostatic lock 156 and transport dynamics 157 of a certain transport process that laid the foundation for the evolution of transport proteins.…”
Section: Engineering Efflux Transport Proteinsmentioning
confidence: 99%